Androgen deprivation therapy for androgen receptor‐positive advanced salivary duct carcinoma: A nationwide case series of 35 patients in The Netherlands. Issue 3 (22nd December 2017) - Boon, Eline; van Boxtel, Wim; Buter, Jan; Baatenburg de Jong, Robert J.; van Es, Robert J. J.; Bel, Miranda; Fiets, Edward; Oosting, Sjoukje F.; Slingerland, Marije; Hoeben, Ann; Tesselaar, Margot E. T.; Jonker, Marianne A.; et al.
Abstract: Background: Salivary duct carcinoma, an aggressive subtype of salivary gland cancer, is mostly androgen receptor‐positive. Only limited data are available on androgen deprivation therapy (ADT). Methods: Patients with advanced androgen receptor‐positive salivary duct carcinoma treated with first‐line ADT were retrospectively evaluated for clinical benefit (ie, partial response [PR] and stable disease, progression‐free survival [PFS] and overall survival [OS]). The OS was compared with patients with advanced salivary duct carcinoma who received best supportive care. Results: Thirty‐four of 35 patients who were ADT‐treated were evaluable: 6 patients had a PR (18%) and 11 had stable disease (32%) leading to a clinical benefit ratio of 50%. The median PFS for the ADT‐treated patients was 4 months and the median duration of clinical benefit was 11 months. The median OS was 17 months versus 5 months in 43 patients receiving best supportive care ( P = .02). Conclusion: We recommend ADT in advanced androgen receptor‐positive salivary duct carcinoma given its response and clinical benefit. © 2017 Wiley Periodicals, Inc. Head Neck, 2017